Estimativa da evaporação e evapotranspiração potencial do reservatório da hidrelétrica de Tucuruí - ZEN, Alexsander de Oliveira (2018)
The phenomena of evaporation and evapotranspiration cause water loss, because evade significant amount of water stored in soils and water reservoirs vegetated, thus can not be ignored in planning activities and management of water resources. This reason, this study aims to estimate evaporation and evapotranspiration of the Tucuruí Hydroelectric Reservoir based on the period of the years 2000 to 2004 by statistical analysis instrument reading of evaporation and empirical methods for estimating evapotranspiration. For evaporation, we used the tools of reading and a Class A tank Evaporimeters Tar, potential evapotranspiration and empirical methods Tank Class A Thonrthwait and Penman-Monteith-FAO, but this is an estimate of the value of the reference evapotranspiration was used as a parameter to overestimation did not occur, because it is a method with international backing. The results of this work show that the instrument for measuring evaporation with values less dispersed was the Class A evaporimeter tank, which generated an average evaporation of the study period in 1459.73 mm / year. The empirical method for estimating potential evapotranspiration closer to the parameter of the Amazon region was the method Class A tank, which generated an estimated average study period of 103.40 mm / month.